1982
DOI: 10.1177/002246698201600303
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Community Survival Skills To Mentally Retarded Adults: A Review and Analysis

Abstract: A revolution in providing residential alternatives for mentally retarded (MR) individuals has made in vivo training a part of the deinstitutionalization process. The literature indicates that institutional teaching programs may not be as effective as in vivo community training. MR adults can acquire a variety of community survival skills — the skills curriculum developers must address when they devise new and innovative community integration experiences. This paper reviews the training procedures and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The independent use of transportation has been identified as one of the key skills required for people with disabilities to be integrated within their communities [4,5]. A study of patterns of community integration 2-5 years postdischarge from brain injury rehabilitation revealed that a high percentage of people who had received severe injuries fell into a 'poorly integrated' group, characterized in part by the absence of shopping or leisure activities outside the home [6].…”
Section: Introductionmentioning
confidence: 99%
“…The independent use of transportation has been identified as one of the key skills required for people with disabilities to be integrated within their communities [4,5]. A study of patterns of community integration 2-5 years postdischarge from brain injury rehabilitation revealed that a high percentage of people who had received severe injuries fell into a 'poorly integrated' group, characterized in part by the absence of shopping or leisure activities outside the home [6].…”
Section: Introductionmentioning
confidence: 99%
“…Bates (in press) has described six methods for determining available community jobs: (a) listing previously successful employment options of past graduates, (b) keeping a record of the frequency with which specific types of jobs appear in classified ads, ( c) obtaining a list of employment openings from local rehabilitation counselors, (d) conducting surveys of local, businesses, (e) utilizing personal contacts with community leaders (e.g., principals, small business operators), and (f) Once a listing of potential jobs has been generated, the specific "survival skills" required in each of the potential job sites is identified. Survival skills are generally thought of as those behaviors that facilitate functioning in the community (Martin, Rusch, & Heal, 1982). In relation to employment, survival skills are those that, when acquired, increase the likelihood of employment and job maintenance (Rusch, 1979).…”
Section: Community-referenced Approachmentioning
confidence: 99%
“…Telephone use has been identifi ed as one of the 10 most important survival skills (Martin et al, 1982). Telephone use has been identifi ed as one of the 10 most important survival skills (Martin et al, 1982).…”
Section: Teaching Health and Safety Skillsmentioning
confidence: 99%